Analisis Pengaruh Penerapan Green Accounting, Kepemilikan Saham Publik, dan Ukuran Perusahaan terhadap Kinerja Keuangan - Hascaryo, Gabriella Putri; Widaryanti, Widaryanti (Jurnal Ilmiah Aset, 2025)
This study aims to analyze and test the influence of green accounting, public share ownership, and company size on financial performance. The independent variables used in this study are green accounting, public share ownership, and company size. The dependent variable in this study is financial performance. This research is a research with a quantitative method with a type of data, namely secondary data obtained from the IDX. The population used is food and beverage companies listed on the IDX for the 2019-2022 period. The selection of samples in this study using the purposive sampling method produced 108 samples, with the number of outliers as many as 5 samples so that the final results of 103 samples were obtained. The analysis technique used is multiple linear regression analysis. The results of this study show that the application of green accounting has no effect on financial performance, public share ownership has no effect on financial performance, and company size has a significant negative effect on financial performance, and the application of green accounting, public share ownership, and company size simultaneously have a positive and significant effect on financial performance.